(untitled) (Our Nature, 2023)
The In-pond raceway aquaculture (IPRA) was developed to increase production that is more controllable and efficient than pond culture system. This study was conducted on commercial scale in IPRA to characterize the water quality and microbial community study within IPRA farms. The IPRA covers an area of ​​2h of traditional pond with 10 raceways, each of 25m× 5m×2.5m of fish culture units. Where monitoring of water quality parameters and microbial abundancy had been studied between inlet and outlet of the raceways during 108 days of culture period. Average water quality parameters and total soluble solid (TSS) over the course of the study was not found to be significantly difference. Nitrite nitrogen, nitrate nitrogen, total ammonia nitrogen, total phosphorus, chlorophyll-a and chemical oxygen demand were higher in outlet than inlets of IPRA. However, average total nitrogen, soluble reactive phosphorus and total soluble solids concentrations were slightly higher in inlets of IPRA there was also insignificance difference of microbial abundance. Therefore, it can be concluded from this study that fishes in raceways consumed nearly all the feed offered and a negligible amount of feed was wasted. So, leftover feed settlement to the bottom of the pond became a concern of no issue, despite the raceway having intensive fish culture thus bringing non-significant differences in water quality parameters between the inlet and outlet of the IPRA system.